Multiple Linear Regression Study of 2,4-Disubstituted 1,5- Benzodiazepine as Potential Antiinfectives: 2,4-Disubstituted 1,5-Benzodiazepine as Potential Antiinfectives - Bhatia Manish Sudesh; Choudhari Prafulla Balkrishna; Ingale Kundan Bhanudas (Iranian Journal of Pharmaceutical Sciences, 2010)
This paper describes 3D-QSAR analysis and biological evaluation of 1,5-benzodiazepine analogues. Benzodiazepine nucleus with its simple structure gives a good opportunity for further modification regarding an increase of its antimicrobial activity. We synthesized a series of benzodiazepine analogues from condensation of various chalcones and halo substituted o-phenelynene diamines. All compounds were assayed in vitro against, E. coli, P. aeruginosa, S. aureus. The models were generated on the Vlife MDS 3.5; selected models showed a correlation coefficient (r2) above 0.9 with cross-validated correlation coefficient (q2) above 0.8, respectively, for all the selected organisms. The 3D-QSAR models generated were externally validated for all models using a test set of 6 molecules for which the predictive r2 (r2-pred) was found to be above 0.45. The results of 3D-QSAR indicate that contours can be used to design some potent antibacterial agents.